IMPROVING THE RSA PUBLIC-KEY ENCRYPTION ALGORITHM BASED ON PARAMETRIC ALGEBRA - Khudoykulov Zarifjon; Khudoynazarov Umidjon (The latest news and research in education, 2025)
This article presents a modification of the RSA public-key cryptographic algorithm based on parametric algebraic operations. The application of parametric multiplication, inversion, and exponentiation operations enhances the algorithm’s exponentiation process through an additional parameter, thereby increasing its cryptographic resilience. The proposed closed-form expression for parametric exponentiation optimizes the computation process and aligns the overall complexity of the algorithm with that of standard RSA. The practical results confirm the functional correctness and efficiency of the improved approach.